Battlefields Tourism: The status of heritage tourism in Dundee, South Africa - van der Merwe, Clinton David (Bulletin of Geography. Socio-economic Series, 2014)
Heritage tourism is a significant contemporary facet of tourism in many developing countries. This paper analyses the economic opportunities for battlefield-heritage tourism in South Africa by examining the battlefields route within KwaZulu-Natal. Through structured interviews with stakeholders and structured questionnaires with visitors and local residents, this research explores the understanding of heritage tourism as well as perceptions of its influence on the physical landscape and gauges the importance of this form of tourism as a driver for local economic development in South Africa. Dundee, a small coal-mining town in KwaZulu-Natal, South Africa – where several battlefields are found, is used as a case study. The study demonstrates that several issues need to be addressed if this niche of cultural and heritage tourism is to be a sustainable and responsible form of tourism in South Africa.